Critical Pedagogy in Nursing Transformational Approaches to Nurse Education in a Globalized World - Dyson, Sue (Palgrave Macmillan UK, 2018)
This book explores the academic processes of nursing education in times of uncertainty around healthcare policy and healthcare provision. Grounded in research examining current theory, policy and culture around nursing pedagogy, Sue Dyson addresses the core issues facing nurses today and argues that the current curriculum no longer reflects or serves contemporary nursing practice. In a time of scandals, cuts in funding and shortfalls in the profession, this book provides an answer to the growing call for a dynamic restructuring of nurse education. Offering a critical analysis of innovative pedagogies for nursing, the author proposes the notion of the co-created curriculum as a way forward for nurse education in the post-Francis era. This will be an invaluable read to academics, practitioners and policy makers in the fields of nursing, medicine, education, education policy and medical sociology.